Reflexión teórica sobre los procesos de actualización curricular de los programas de psicología - Guerrero Escobar, Carmen Beatriz (Pensando Psicología, 2010)
The Faculty of Psychology from the Universidad Cooperativa de Colombia, Popayán, is currently developing the updating curriculum project, whose general objective is ensuring the academic quality of Psychology program through the implementation of an improvement plan that provides the curriculum restructuring related to the provisions of 3461 law ranking decree from 2003 and national guidelines from Ecaes Project, regulations that must be associated to social relevance and meaning of such curricular structure. The theoretical framework incorporated elements by Rebeca Puche Navarro and Armando Aguilera Torrado, who work on aspects related to the development and interpretation of academic Psychology in Colombia and higher college teaching. Likewise, general college education issues were taken from Morín and Tunnermann. Finally, the division of an improvement plan in connection with the structuring of micro-curri-culum and the adjustment proposal to the curriculum.